Flow bioreactors as complementary tools for biocatalytic process intensification - Tamborini, Lucia; Fernandes, Pedro; Paradisi, Francesca; Molinari, Francesco (Elsevier, 2017)
Biocatalysis has widened its scope and relevance since new molecular tools, including improved expression systems for proteins, protein and metabolic engineering, and rational techniques for immobilization, have become available. However, applications are still sometimes hampered by low productivity and difficulties in scaling up. A practical and reasonable step to improve the performances of biocatalysts (including both enzymes and whole-cell systems) is to use them in flow reactors. This review describes the state of the art on the design and use of biocatalysis in flow reactors. The encouraging successes of this enabling technology are critically discussed, highlighting new opportunities, problems to be solved and technological advances.